2015
DOI: 10.1038/srep13249
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glycogen synthase kinase-3 beta induces apoptosis and mitotic catastrophe by disrupting centrosome regulation in cancer cells

Abstract: Glycogen synthase kinase-3 beta (GSK-3β) has been investigated as a therapeutic target for numerous human diseases including cancer because of their diverse cellular functions. Although GSK-3β inhibitors have been investigated as anticancer reagents, precise biological mechanisms remain to be determined. In this study, we investigated the anticancer effects of GSK-3β inhibitors on cancer cell lines and observed centrosome dysregulation which resulted in abnormal mitosis. Mitotic checkpoints sensed the mitotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 45 publications
4
43
0
Order By: Relevance
“…Through this, GSK3β acts as a negative regulator by inducing up‐regulation of WNT/β‐catenin signaling . On the other hand, as a positive regulator, GSK3β modulates mTOR activity by regulating formation of TSC1‐2 complexes, which, in turn, influence mTOR/Raptor complex formation and the activity of downstream effectors such as ribosomal protein S6 kinase (S6K) . Our study identified that mTOR/Raptor complex was affected by GSK3β and it also contribute to drug response through decreased the levels of active mTOR (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Through this, GSK3β acts as a negative regulator by inducing up‐regulation of WNT/β‐catenin signaling . On the other hand, as a positive regulator, GSK3β modulates mTOR activity by regulating formation of TSC1‐2 complexes, which, in turn, influence mTOR/Raptor complex formation and the activity of downstream effectors such as ribosomal protein S6 kinase (S6K) . Our study identified that mTOR/Raptor complex was affected by GSK3β and it also contribute to drug response through decreased the levels of active mTOR (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Next, we tested whether inhibition of GSK3β causes necroptosis in PDAC cells, although impaired GSK3β activity reportedly triggers apoptosis 29 . Treatment with GSK3β inhibitors (XXVI or AR-A014418) resulted in the death of PANC1 and PANC2.03 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7c). Since centrosome dysregulation-associated mitotic defects could result in genome instability and cell apoptosis134546, we examined whether USP9X-promoted CEP131 stabilization plays a role in genome stability and cell death. Indeed, we demonstrated that either USP9X or CEP131 depletion resulted in marked accumulation of γH2AX (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%